2020
DOI: 10.3390/su12229695
|View full text |Cite
|
Sign up to set email alerts
|

Tourism Accessibility and Its Impact on the Spiritual Sustainability of Sacred Sites

Abstract: Religious heritage sites are defined by their nature, both religious and non-religious (historical, social, cultural, etc.), as being pilgrimage destinations, as well as tourist attractions. The main aim of this paper is to determine whether there is a relationship between tourism accessibility and the concept of spiritual sustainability. Spiritual sustainability is presented in the paper by analyzing the concept of a sacred place and the connection it may have with tourism development. The authors have attemp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 67 publications
1
12
0
1
Order By: Relevance
“…On the other hand, the results of Aulet and Duda [2020], which examined the relationship between religious heritage sites and tourism from the perspective of spiritual sustainability, showed that the lack of accessibility positively affects the spiritual sustainability of the sites. It is also important to carefully consider the negative aspects that improving accessibility may have on the psychological state of local worshippers.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the results of Aulet and Duda [2020], which examined the relationship between religious heritage sites and tourism from the perspective of spiritual sustainability, showed that the lack of accessibility positively affects the spiritual sustainability of the sites. It is also important to carefully consider the negative aspects that improving accessibility may have on the psychological state of local worshippers.…”
Section: Discussionmentioning
confidence: 99%
“…sacredness and the spiritual connections between the sites and people) for instrumental benefits (e.g. tourism revenue) 69 .…”
Section: Synergies and Trade-offs Between Mechanismsmentioning
confidence: 99%
“…The environmental degradation associated with intensive tourism combined with the risks of changing livelihood structure may result in significant loss of local knowledge systems and skills 71 . In other cases, the inappropriate planning of tourism activities can hinder the educational value of historically, culturally, and ecologically important areas 69,72 .…”
Section: Synergies and Trade-offs Between Mechanismsmentioning
confidence: 99%
“…It takes place in a particular geographical area that forms part of a widely known cultural landscape. The complexity of the elements of the destination, its space's existence dictates its diversity and shape, which is the result of changes in tourists' inspiration, behaviors, and wishes (Aulet & Duda, 2020). Religious tourism the accessibility of the place really matters to many tourists, the place where they could stay, the price and the popularity of the place and events as well (Giușcă et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The religious significance is associated with the religious values, time and events being set by the religious organization. In the context of religious tourism, facilities, tourist activities and services are essential (Aulet & Duda, 2020). As a result, many people seek religiously invigorating spiritual and cultural experiences in order to grow and be enlightened by what they discover at a location (Nicolaides, 2016).…”
Section: Introductionmentioning
confidence: 99%